1992
DOI: 10.1037/0278-7393.18.4.749
|View full text |Cite
|
Sign up to set email alerts
|

The process of lexical decision: More words about a parallel distributed processing model.

Abstract: Central to Seidenberg and McClelland's (1989) parallel distributed processing (PDP) model's account of lexical decision is the assumption that performance is determined by the amount of overlap in the distribution of the orthographic error scores between words and nonwords. The present experiment demonstrates lexical decision performance that is independent of the distribution of orthographic error scores between words and nonwords. Furthermore, the orthographic error scores from the model capture no variance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
39
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 38 publications
0
39
0
Order By: Relevance
“…Here we discuss how the remaining three issues-acquired phonological dyslexia, developmental dyslexia, and lexical decision-may be accounted for in light of these findings. We also consider three other empirical findings that have been interpreted as providing evidence against the current approach-pseudohomophone effects (Buchanan & Besner, 1993;Fera & Besner, 1992;McCann & Besner, 1987;Pugh, Rexer, & Katz, 1994), stimulus blocking effects (Baluch & Besner, 1991;Coltheart & Rastle, 1994;Monsell et al, 1992), and the recent finding that naming latencies for exception words are influenced by the position of the exceptional correspondence (Coltheart & Rastle, 1994). Acquired Phonological Dyslexia.…”
Section: Additional Empirical Issuesmentioning
confidence: 99%
See 3 more Smart Citations
“…Here we discuss how the remaining three issues-acquired phonological dyslexia, developmental dyslexia, and lexical decision-may be accounted for in light of these findings. We also consider three other empirical findings that have been interpreted as providing evidence against the current approach-pseudohomophone effects (Buchanan & Besner, 1993;Fera & Besner, 1992;McCann & Besner, 1987;Pugh, Rexer, & Katz, 1994), stimulus blocking effects (Baluch & Besner, 1991;Coltheart & Rastle, 1994;Monsell et al, 1992), and the recent finding that naming latencies for exception words are influenced by the position of the exceptional correspondence (Coltheart & Rastle, 1994). Acquired Phonological Dyslexia.…”
Section: Additional Empirical Issuesmentioning
confidence: 99%
“…Two other, somewhat overlapping sets of empirical findings have been viewed as problematic for the current approach: pseudohomophone effects (Buchanan & Besner, 1993;Fera & Besner, 1992;McCann & Besner, 1987;Pugh et al, 1994) and blocking effects (Baluch & Besner, 1991;Coltheart & Rastle, 1994;Monsell et al, 1992). The first set involves demonstrations that, under a variety conditions, pseudohomophones (i.e., nonwords with pronunciations that match that of a word; e.g., BRANE) are processed differently than orthographically-matched nonpseudohomophonic nonwords (e.g., FRANE).…”
Section: Additional Empirical Issuesmentioning
confidence: 99%
See 2 more Smart Citations
“…As evidence that phonology does play a role in the lexical decision task, researchers have shown that nonword response latencies are longer to pseudohomophones (e.g., nale) than to orthographically matched pseudowords (e.g., nalp; Coltheart, Davelaar, Jonasson, & Besner, 1977;Fera & Besner, 1992;McCann, Besner, & Davelaar, 1988;Rubenstein, Lewis, & Rubenstein, 1971;Seidenberg, Petersen, MacDonald, & Plaut, 1996), implying that the pseudohomophone accesses the representation of its base word (e.g., nail ), and that this base word representation slows the processing of the pseudohomophone. Because the pseudohomophone effect has become central to models of word recognition (Ziegler, Jacobs, & Klüppel, 2001), it is critical that we understand fully the processes underlying the effect.…”
mentioning
confidence: 99%